THU0453 Biomarkers of Bone and Cartilage Remodeling in OA is Strongly Associated with Pain and Obesity: Data from Two Phase 3 Randomized Clinical Trials in Symptomatic Knee OA. (9th June 2015) - Bihlet, A.R.; Bay-Jensen, A.-C.; Karsdal, M.A.; Byrjalsen, I.; Riis, B.J.; Christiansen, C.; Andersen, J.R.; Musa, K.; Alexandersen, P.
Abstract : Background: Cartilage and bone are the central tissues affected by osteoarthritis (OA). Remodeling of these tissues can be measured by soluble biomarkers. Recent data has shown that urinary type II collagen C-terminal telopeptide (u-CTX-II) is a biomarker of cartilage and subchondral bone turnover. Bone resorption may be quantified by type I collagen cross-linked C-terminal degradation in serum (s-CTX-I). Objectives: The purpose of this analysis was to investigate the association between cartilage and bone remodeling, measured by u-CTX-II and s-CTX-I, and clinically recorded knee pain and KL score, as well as the OA risk factor Body Mass Index (BMI). Methods: Fasting serum (n=767) and urine (n=620) samples were collected at baseline from patients with painful knee OA participating in the placebo arms of two phase III RCTs (NCT00486434 and NCT00704847 ). Creatinine-corrected u-CTX-II (IDS PLC, United Kingdom]) and s-CTX-I (Roche, United Kingdom) were measured. The relationship between the biomarkers and baseline-reported WOMAC pain level of the target knee, radiographic OA score (KL) and BMI were analyzed by Spearman's correlations on log-transformed biomarker data and by multiple regression analysis (OLS), where WOMAC, KL score or BMI were set as the dependent variable and biomarkers, BMI and age as covariates, adjusted for gender. Results: Both CTX-I and CTX-II were significantly correlated to BMI (r=-0.26, p<0.0001, r=-0.09, p=0.0013) after adjustment for age and gender. Levels of CTX-II significantly correlated with WOMAC pain (β=19.8, p=0.022), which remained after adjustment (β=20.4, p=0.019). CTX-II was likewise correlated with KL score before (β=0.26, p<0.0001) and after (β=0.25, p<0.0001) adjustment. Levels of s-CTX-I was not statistical significantly correlated with WOMAC pain (β=4.73, p=0.64), nor after adjustment (β=6.06, p=0.57). s-CTX-I was not statistical significantly with KL score before (β=0.08, p=0.061), but weakly so after (β=0.11, p=0.018) adjustment. Conclusions: This cross-sectional analysis of data from a large clinical trial dataset shows strong correlations between the biomarkers CTX-I, CTX-II and pain and obesity. These findings may be a reflection of high mechanical joint loading caused by overweight, contributing to pathological bone and cartilage wear which could lead to increased pain. Longitudinal data to support this hypothesis is needed. These data indicate that CTX-I and CTX-II may assist in identifying disease drivers of a specific, painful OA phenotype to be further investigated. Acknowledgements: We wish to thank the participants and investigators of the CSMC021C2301/2 trials. Disclosure of Interest: A. Bihlet Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, A.-C. Bay-Jensen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, B. Riis Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, C. Christiansen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, J. Andersen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, K. Musa Employee of: Nordic Bioscience, P. Alexandersen Grant/research support from: Nordic Bioscience